Antimicrobial Resistance of Secondary Bacterial Infections in Patients Hospitalized with Covid-19 - Afrah Adnan Hashim, Alyaa Maan Abdelhameed (Pakistan Journal of Medical & Health Sciences, 2022)
Coronavirus disease 2019 (COVID-19) is an emerging serious global health problem. It has been recognised for a considerable time-period, that viral respiratory infections predispose patients to bacterial infections, and that these co-infections have a worse outcome than either infection on its own. This study was carried out on 100 samples of sputum from COVID-19 patients. During the laboratory diagnosis, 156 bacterial isolates were obtained from the positive samples . The Gram-positive bacteria isolates included Strptococcus pneumonia 64(40%) Streptococcus pyogenes, 7 (4%), Streptococcus mitis 1 (1%) Streptococcus mutus 1(1%) , Streptococcus parasanguinis 1(1%) Staphylococcus eidermidis 10(6%), staphylococcus aureus 4 (2%), Micrococcus lutus,1 (1%). Whereas, Gram-negtive bacteria included Pseudomonas aeruginosa 9 (6%), E coli 10 (6%), Serratia marcescens, 3 (2%), Klebsiella pneumonia 31 (19%), H.influenzae 10 (6%) Acinetobacter baumannii , 4 (2%) .The isolates varied in their response against the antibiotics ; and Gram positive bacteria were significantly (p<0.05) more sensitive to the antibiotic then Gram negative. To detect the Streptococcus pneumonia isolates , the house keeping Eno genes was screened. Results showed that all the isolates, had Eno gene (100%). Furthermore, This study was carried out in order to detect tet-L and ermB gene in 10 S.pneumonia isolates . genes were Results showed that all the isolates, numbering 10, had both tetL and ermB genes(100%).